EDIN Scale Implemented by Gestational Age for Pain Assessment in Preterms: A Prospective Study. (8th February 2017) - Raffaeli, G.; Cristofori, G.; Befani, B.; De Carli, A.; Cavallaro, G.; Fumagalli, M.; Plevani, L.; Mosca, F.
Abstract : Background. Chronic neonatal pain can lead to long-term adverse effects on the immature brain. EDIN scale for prolonged pain might not be fully suitable for premature infants. We aimed to test a modified EDIN scale, adding postmenstrual age (PMA) as a sixth item (EDIN6). Methods. In a two-phase prospective study, pain was assessed in all neonates admitted in our NICU. In T 1 EDIN was applied; in T 2 EDIN6 with additional scores of 2, 1, and 0, respectively, for 25–32, 33–37, and >37 weeks PCA was tested. Scores > 6 suggested pain. The nursing staff was given a questionnaire to evaluate EDIN and EDIN6. Results. A total of 15960 pain assessments were recorded (8693 in T 1; 7267 in T 2). With EDIN6, cumulative detection of pain almost tripled (117/7267 versus 52/8693, p = 0.001 ). Main differences were found among less mature categories (50/1472 versus 17/1734, p = 0.001 in PCA 25–32; 26/2606 versus 10/4335, p = 0.001 in PMA 33–37; 41/3189 versus 25/2624, p = 0.26 in PMA > 37). Adequacy of pain assessment in lower PMA was judged "medium-high" in 13, 4% of nurses in T 1 and 71, 4% in T 2. Conclusions. EDIN6 may allow improved evaluation of pain in preterm infants.